Pengaruh Budaya Organisasi Dan Kepemimpinan Terhadap Kinerja Pegawai Dengan Komitmen Organisasi Sebagai Variable Intervening Pada Dinas Pengelolaan Keuangan Daerah Provinsi Sumatera Barat - Muhammad Diaurridha (Jurnal Metaverse ADPERTISI, 2022)
This study aims to determine the influence of leadership and organizational culture on employee performance with organizational commitment as an intervening variable at the West Sumatra Provincial Financial Management Office. The research population is all employees who work in the financial management department of the West Sumatra region. The sampling method is simple random sampling. The number that can be used as an analytical tool is 100 respondents. The data analysis method used in this research is multilevel linear regression analysis. The results of the study show that (1) the organizational culture variable has a significant effect on the performance of the employees of the Regional Financial Management Office of West Sumatra Province. (2) the leadership variable has a significant effect on the performance of the employees of the Regional Financial Management Office of West Sumatra Province. (3) the organizational commitment variable has a significant effect on the performance of the employees of the Regional Financial Management Office of West Sumatra Province. (4) organizational commitment as an intervening variable has a significant effect on the organizational culture of the Regional Financial Management Office of West Sumatra Province. (5) organizational commitment as an intervening variable affects the leadership of the Regional Financial Management Office of West Sumatra Province. (6) organizational commitment as an intervening variable does not play a role in mediating organizational culture on the performance of employees of the Regional Financial Management Office of West Sumatra Province. (7) organizational commitment as an intervening variable plays a role in mediating leadership has a significant effect on the performance of employees of the Regional Financial Management Office of West Sumatra Province. The implications of this research can contribute to the idea that the variable of organizational commitment can mediate the relationship between organizational culture and leadership on the performance of the employees of the Regional Financial Management Office of West Sumatra Province. This indicates that if the organization wants to increase organizational commitment to achieve better performance, it is by applying a good organizational culture and leadership style, proportional to its employees.